SULFONATION OF NYLON-6 BY SOLID-PHASE REACTION - KWAK, S; LEE, SY (ELSEVIER SCI LTD, 1994)
Sulfonation of nylon-6 has been widely studied via solution phase reaction processes, which involve dissolution of the base polymer in a strong solvent. In this paper, novel solid phase reaction technology was adopted to induce the addition of the sulfonate side chain onto the backbone of nylon-6 using 1,3-propane sultone. The reaction of the polymer with the reagent, which was catalysed by dimsyl anions, was carried out at 65-degrees-C in a specially designed, well-mixed reactor. The reaction materials remained as free-flowing powders through the process. A sulfonate level of 1.32 mol% was achieved. The conversion of the 1,3-propane sultone was 23.3%. The sulfonation was qualitatively identified with FTi.r. and d.s.c. Its sulfonate level was determined by quantitative measurement of sulfur and nitrogen content of the treated polymer.
Keywords: GRAFT-COPOLYMERIZATION; MOLECULAR COMPOSITES